2020
DOI: 10.1111/anae.15299
|View full text |Cite
|
Sign up to set email alerts
|

PROSPECT guideline for tonsillectomy: systematic review and procedure‐specific postoperative pain management recommendations

Abstract: Tonsillectomy is one of the most frequently performed surgical procedures; however, pain management remains challenging. Procedure-specific efficacy as well as specific risks of treatment options should guide selection of pain management protocols based on evidence and should optimise analgesia without harm. The aims of this systematic review were to evaluate the available literature and develop recommendations for optimal pain management after tonsillectomy. A systematic review utilising preferred reporting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 147 publications
(235 reference statements)
2
56
0
4
Order By: Relevance
“…However, as for the smell, olive oil is of some aroma, and its intake has many health benefits for children ( 21 ). Adding olive oil to honey can help increase its intake, while oral administration of honey is also recommended for other medical needs, such as postoperative analgesia for tonsillectomy and oral mucositis treatment in children ( 22 , 23 ). Honey contains 65–80% (w/w) of glucose and fructose ( 24 ), and it still tastes very sweet even diluted twice, sweeter than the aqueous solution with same content (w/w) of sucrose, because sucrose (a disaccharide) is with lower sweetness than monosaccharide glucose and fructose.…”
Section: Discussionmentioning
confidence: 99%
“…However, as for the smell, olive oil is of some aroma, and its intake has many health benefits for children ( 21 ). Adding olive oil to honey can help increase its intake, while oral administration of honey is also recommended for other medical needs, such as postoperative analgesia for tonsillectomy and oral mucositis treatment in children ( 22 , 23 ). Honey contains 65–80% (w/w) of glucose and fructose ( 24 ), and it still tastes very sweet even diluted twice, sweeter than the aqueous solution with same content (w/w) of sucrose, because sucrose (a disaccharide) is with lower sweetness than monosaccharide glucose and fructose.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that percutaneous peripheral nerve stimulation can be used to treat acute postoperative pain of various types of surgeries [ 32 ]. Acupuncture intervention and transcutaneous electrical nerve stimulation (TENS), being similar to percutaneous peripheral nerve stimulation, have been proved to be effective for relieving postoperative pain of neck surgery [ 9 , 10 , 33 ], tonsillectomy [ 7 , 11 , 34 ], back surgery [ 5 ], dental procedures [ 7 , 35 ], and knee replacement [ 7 ]. Our previous clinical study [ 33 ] also showed that EA of LI18 and LI4-PC6 had a good effect in inducing analgesia and controlling the mean arterial pressure (MAP) and heart rate (HR), and reduced the anesthetic dose required by patients undergoing thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Each year, 500,000 individuals in the United States undergo tonsillectomy [ 3 ], which is often performed during the daytime in an ambulatory setting by otolaryngologists and pediatricians [ 4 ]. Although the French Oto-Rhino-Laryngology Head and Neck Surgery Society [ 5 ] and other researchers [ 6 ] have published guidelines for post-tonsillectomy pain management in adults and children, respectively, pain management remains challenging and poorly managed in clinical practice [ 7 ]. Postoperative pain after tonsillectomy is related to the indications and surgical techniques [ 8 ].…”
Section: Introductionmentioning
confidence: 99%